2003
DOI: 10.1093/molbev/msg049
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Age of Extant Ephedra Using Chloroplast rbcL Sequence Data

Abstract: The distinctive gymnosperm genus Ephedra is sometimes considered to have originated over 200 million years (Myr) ago on the basis of "ephedroid" fossil pollen. In this article we estimate the age of extant Ephedra using chloroplast rbcL gene sequences. Relative rate tests fail to reject the null hypothesis of equal rates of nucleotide substitution of the rbcL sequences among three landmark lineages (Gnetales, Pinaceae, and Ginkgo). The most divergent sequences we have found in Ephedra differ by only 7 bp for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 21 publications
3
33
0
4
Order By: Relevance
“…Recent molecular phylogenetic studies also revealed that three monotypic families or orders were put into same clade separating other gymnosperms, and support the previous taxonomic treatments (Hasebe et al 1992a, b;Huang and Price 2003;Rydin et al 2004). In cytological studies of Gnetopsida, Ephedra (n=7), Gnetum (n=11) and Welwitschia (n=21), their karyotypes were quite different in basic number, chromosome morphology and genome size (Khoshoo and Ahuja 1963;Chouhdry 1984;Hizume et al 1993;Leitch et al 2001).…”
Section: Introductionsupporting
confidence: 60%
See 2 more Smart Citations
“…Recent molecular phylogenetic studies also revealed that three monotypic families or orders were put into same clade separating other gymnosperms, and support the previous taxonomic treatments (Hasebe et al 1992a, b;Huang and Price 2003;Rydin et al 2004). In cytological studies of Gnetopsida, Ephedra (n=7), Gnetum (n=11) and Welwitschia (n=21), their karyotypes were quite different in basic number, chromosome morphology and genome size (Khoshoo and Ahuja 1963;Chouhdry 1984;Hizume et al 1993;Leitch et al 2001).…”
Section: Introductionsupporting
confidence: 60%
“…When the CMA-banding or fluorescence in situ hybridization (FISH) using rDNA probe are applied to chromosomes of many Ephedra species, a deposit of information on satellite will be expected to reveal inter-and/or intra-specific variation and relationships among species. Comparing of the grouping of species on the basis of satellite with molecular phylogenetic trees (Huang and Price 2003;Ickert-Bond and Wojciechowski 2004;Rydin et al 2004) will revel the phylogenetical significance of satellites in Ephedra. Mehra and Khitha (1981) reported that heterozygous and homozygous satellites on certain chromosomes in E. foliate and proposed presence of XY-type sex chromosome system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, even with ancient and relatively good fossil records, such as those of Calycanthaceae, Chloranthaceae, Ephedra, Nothofagus or Nymphaeaceae, seeming contradictions between paleobotanical studies [11,12] and molecular clock studies can arise [47,[66][67][68][69]. These dissolve when it is understood that the young molecular estimates for living clades in these families simply indicate that a diversification in an area is young (Figure 1a).…”
Section: Glossarymentioning
confidence: 99%
“…Despite limited sampling of species and low resolution of molecular characters, modern molecular systematic studies have consistently suggested that the genus Ephedra can be subdivided into three groups according to geographic ranges of species and bract nature of female cones can not be used for classification of the genus because they are adaptive features with high probability of parallel evolution (Huang and Price, 2003;Ickert-Bond and Wojciechowski, 2004;Rydin et al, 2004;Huang et al, 2005;Ickert-Bond et al, 2009;Rydin and Korall, 2009). Additional study suggests that Ephedra has three distinct seed dispersal syndromes including membranous bracts, coriaceous bracts, and fleshy bracts, and sect.…”
Section: Introductionmentioning
confidence: 99%